Occupational Exposure to Metals in Shooting Ranges: A Biomonitoring Study - Eline Vandebroek; Vincent Haufroid; Erik Smolders; Luc Hons; Benoit Nemery (Elsevier, 2019)
Background: Lead (Pb) exposure in shooting ranges has been reduced by various measures such as jacketed ammunition and lead-free primers. Nevertheless, this may lead to exposure to other metals, potentially resulting in adverse health effects. Methods: In a cross-sectional study, 35 subjects from seven different shooting ranges were studied: four shooting instructors, 10 police officers, 15 Special Forces, and six maintenance staff members. Metals and metalloids were determined in blood and urine by inductively coupled plasma-mass spectrometry. Results: The concentrations of most elements did not differ significantly between groups or compared to reference values, except for Sb and Pt in urine and Pb in blood. Mean values for Sb were considerably higher in urine from the Special Forces (0.34 μg/L), the maintenance staff (0.13 μg/L), and shooting instructors (0.32 μg/L) compared to the police officers before shooting (0.06 μg/L) and a Belgian reference value (0.04 μg/L). For Pt, the Special Forces showed higher mean urinary concentrations (0.078 μg/L) compared to a Belgian reference value (<0.061 μg/L). Mean values for blood lead were markedly higher in the Special Forces (3.9 μg/dL), maintenance staff (5.7 μg/dL), and instructors (11.7 μg/dL) compared to police officers (1.4 μg/dL). One instructor exceeded the biological exposure index for blood Pb (38.8 μg/dL). Conclusion: Since both Pb and Sb were found to be higher in shooting range employees, especially among frequent shooters, it is advisable to provide appropriate protective equipment, education, and medical follow-up for shooting range personnel in addition to careful choice of ammunition. Keywords: Biomonitoring, Metals, Occupational health